Penerapan Model Visual Auditori Kinestetik (VAK) Untuk Meningkatkan Hasil Belajar IPA Siswa Sekolah Dasar - Latri Latri; Muhammad Amran; Asbullah Rahman; Mujahidah Mujahidah (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
This research is a classroom action research which aims to find out how the VAK learning model is applied to improve students' science learning outcomes. The research method is classroom action research. Data analysis techniques in this study are data reduction, data description and conclusion. The results showed that there was an increase, both in teacher and student activities and learning outcomes in science subjects from cycle I, it was found that 12 out of 23 students obtained a complete score (52.17%) and 11 out of 23 students (47.82%) ) who received an incomplete score so that based on the completeness obtained it was still in the Enough category (C) increasing in cycle II it was found that 20 out of 23 students (85.13%) got a complete score and 3 out of 23 students (13.04 %) who obtained an incomplete score in the Good category (B) which shows that the learning objectives were achieved thus, the use of learning models can improve students' science learning outcomes.